The Geographical Information System (Italian Journal of Public Health, 2008)
The Geographical Information System, normally called GIS, is a tool for representing spatial relationships and real processes with the help of a model. A GIS is a system of hardware, software and staff for collecting, managing, analysing and representing geospatial information. For example, we can study the evolution of an infectious disease in a certain territory, perform market analysis, or locate the best ways to choose a new industrial site. In substance, it is data manipulation software for that allows us to have, both the graphic component, that is a territorial representation of the reality that you want to represent, and the data components in the form of a database or more commonly, calculation sheets. Geographical data are divided in spatial data and attribute data: Spatial data are recorded as points, lines and polygons (vectorial structure). In other words, the survey systems have been projected to acquire information in accordance to elementary cells corresponding to a territorial grid (raster structure). It also includes remote sensing data.